2018
DOI: 10.20473/jmtt.v11i2.10493
|View full text |Cite
|
Sign up to set email alerts
|

Price Earnings Ratio dan Pendapatan Saham Perusahaan Non Keuangan di Bei

Abstract: This research aims to examine which ratio between PER, PEG, and PERG that can better predict the stock returns of the firms, in addition to analyze the effect of each that ratio onstock return. The research sample consist of 310 non-financial firms in IDX during the period of 2010-2016. In this study, multiple linear regression methods have been conducted to explain the effect of PER, PEG, and PERG with control variable SIZE, M/B, FLEV, and DPRon stock return. The results indicate that PERG can explain stock r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 8 publications
0
9
0
9
Order By: Relevance
“…If viewed from Financial management, STTPA's decision to only use SPP, donations, and sponsorships as Operational Financing sources reflects two Financial management principles related to Decision Making Financial (Sudana, 2011), namely the principle of avoiding risk and the principle of signals. Theological Seminary Providensia Adonay only uses the three forms of financing as a source of funding because the institution wants to avoid the risk of using funding sources that can damage its image as a Christian education institution and not give negative signals to Christian communities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If viewed from Financial management, STTPA's decision to only use SPP, donations, and sponsorships as Operational Financing sources reflects two Financial management principles related to Decision Making Financial (Sudana, 2011), namely the principle of avoiding risk and the principle of signals. Theological Seminary Providensia Adonay only uses the three forms of financing as a source of funding because the institution wants to avoid the risk of using funding sources that can damage its image as a Christian education institution and not give negative signals to Christian communities.…”
Section: Resultsmentioning
confidence: 99%
“…According to Sudana (2011), there are several principles behind Decision Making about Financial, namely the principle of personal interest behavior, the principle of avoiding risk, the principle of diversification, the principle of adding benefits, the principle of capital, the principles of capital market efficiency, the principle of balance risk and return time money.…”
mentioning
confidence: 99%
“…Therefore, companies that do not record profit growth will affect PER and PEG, which then impact stock returns, which indicates the level of welfare of investors. However, Sudana and Maulidiyah (2018) researched PER, PEG, and PEG adjusted for risk on stock returns and found that PER, PEG, and PERG did not influence stock returns. Meanwhile, research by Ghanbarian et al (2014) argues that PER and PEG affect stock returns by finding that stock returns with PEG adjustment are better than stock returns with PER.…”
Section: Discussion Per's Relationship With Pegmentioning
confidence: 99%
“…Pengertian struktur modal menurut (Zainul Arifin, 2018) struktur modal adalah sumber data yang tertanam dalam perusahaan dengan jangka waktu yang panjang. Menurut (Sudana, 2019) struktur modal dikaitkan dengan belanja jangka panjang perusahaan yang dibandingkan dengan utang jangka panjang dan modal sendiri. Berdasarkan pendapat diatas, disimpulkan bahwa struktur modal merupakan sumber modal perusahaan dari hutang jangka panjang dan ekuitas yang digunakan untuk memenuhi kebutuhan perusahaan.…”
Section: Studi Literaturunclassified